2020
DOI: 10.1007/s00198-020-05495-w
|View full text |Cite
|
Sign up to set email alerts
|

IQ driving QI: the Asia Pacific Consortium on Osteoporosis (APCO): an innovative and collaborative initiative to improve osteoporosis care in the Asia Pacific

Abstract: Summary Asia Pacific Consortium on Osteoporosis (APCO) comprises of clinical experts from across the Asia Pacific region, uniting to develop solutions to problems facing osteoporosis management and care. The vision of APCO is to reduce the burden of osteoporosis and fragility fractures in the Asia Pacific region. Introduction The Asia Pacific (AP) region comprises 71 countries with vastly different healthcare systems. It is predicted that by 2050, more than half the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Adoption of such strategies would lessen the burden of osteoporosis in this vast region that accounts for more than 60% of the world’s population [ 5 ]. We have previously described APCO’s raison d’etre , conception and launch, vision, mission, and priority initiatives [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of such strategies would lessen the burden of osteoporosis in this vast region that accounts for more than 60% of the world’s population [ 5 ]. We have previously described APCO’s raison d’etre , conception and launch, vision, mission, and priority initiatives [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Asia Pacific Consortium on Osteoporosis (APCO) is an independent, apolitical, and nonpartisan organization comprised of osteoporosis experts from 19 AP countries and regions. ( 15 ) It represents many key osteoporosis stakeholders and multiple medical and surgical specialties. APCO has tasked itself to develop tangible solutions to the substantive challenges involving osteoporosis management and fracture prevention in this most populated and fastest growing region of the world.…”
Section: A Potential Solutionmentioning
confidence: 99%
“…A survey that we executed in 2020 revealed that the AP region had 18 extant CPGs. ( 15 ) When we analyzed the CPGs, we observed that they were published by different learned bodies, differed in format, and diverged strikingly in the guidance they provided. It was observed that some countries in our region had no guidelines and in others they were out of date; in other countries, guidelines prepared by specialty and subspecialty societies addressed a narrower spectrum of interest limited to the providers in that society.…”
Section: A Potential Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…APCO is comprised of 39 experts in osteoporosis from 19 countries and regions. 4 APCO determined that the existing clinical guidelines for osteoporosis in countries in the Asia-Pacific were too varied in scope and recommendations, through a comprehensive and comparative review. In addition, there are many low-and middle-income countries (LMICs) where no guidelines exist.…”
mentioning
confidence: 99%